Neformalno izobraževanje fizikalnih vsebin in mladinsko raziskovalno delo: Mladi raziskovalci, raziskovalni tabori in festivali - Slavinec , Mitja; Klemenčič, Eva (University of Maribor Press, 2024)
Informal Education of Physics Topics and Young Research Work: Young Researchers, Research Camps, and Research Fairs. This learning material is inteded for students of educational physics, future teachers. Informal education is an important complement to formal forms of education at all levels of education, as it supports the development of key competencies and encourages young people to engage in research. Our focus is on youth research work and research camps. Since teachers act as mentors to young researchers, we present the process and guidelines for the preparation and presentation of young research project, with an emphasis on the fields of physics and astronomy. We acquaint readers with a range of research camps and events held in Slovenia, and provide a detailed presentation of the astronomy camp in which physics teachers also participate.